2011
DOI: 10.1177/1941738111403122
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Balance Error Scoring System

Abstract: Context:The Balance Error Scoring System (BESS) is commonly used by researchers and clinicians to evaluate balance.A growing number of studies are using the BESS as an outcome measure beyond the scope of its original purpose.Objective:To provide an objective systematic review of the reliability and validity of the BESS.Data Sources:PubMed and CINHAL were searched using Balance Error Scoring System from January 1999 through December 2010.Study Selection:Selection was based on establishment of the reliability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
344
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(374 citation statements)
references
References 34 publications
5
344
0
6
Order By: Relevance
“…Of the methods we analyzed, ImPACT and BESS have been established as viable tests to assess postconcussion recovery. [23][24][25] However, our findings suggested that postconcussion, testing the DLEC stance on the WBB with analytic balance software may be an alternative to the BESS for assessing postural stability and may provide information to supplement the neurocognitive information provided by ImPACT. Furthermore, the WBB may be more sensitive than the BESS to postconcussion changes in balance.…”
Section: Discussionmentioning
confidence: 48%
“…Of the methods we analyzed, ImPACT and BESS have been established as viable tests to assess postconcussion recovery. [23][24][25] However, our findings suggested that postconcussion, testing the DLEC stance on the WBB with analytic balance software may be an alternative to the BESS for assessing postural stability and may provide information to supplement the neurocognitive information provided by ImPACT. Furthermore, the WBB may be more sensitive than the BESS to postconcussion changes in balance.…”
Section: Discussionmentioning
confidence: 48%
“…35,36 The test consists of 3 stance conditions (double leg, single leg, tandem); each stance is performed with eyes closed on both normal firm flooring and a mediumdensity foam surface. Inability to maintain stance or eye opening is deemed an error and is recorded as a quantitative measurement of postural instability.…”
Section: Efficacy: Balance Assessmentmentioning
confidence: 99%
“…The scoring system BESS (balance error scoring system), is a test commonly used by clinical investigators [1][2][3]. However, there is an increase of studies that couple the BESS system, as a measure of results beyond the scope of its original purpose [3] introducing the field of sport.…”
mentioning
confidence: 99%
“…However, there is an increase of studies that couple the BESS system, as a measure of results beyond the scope of its original purpose [3] introducing the field of sport. Originally this test was created to evaluate postural control [2], postural instability after a concussion [1,4] or after an uncle injury [5].…”
mentioning
confidence: 99%